A speaking choir of dead people: the making of Recordare - Bernardini, Nicola (Anais do Simpósio Brasileiro de Computação Musical; 2025: Anais do XIX Simpósio Brasileiro de Computação Musical, 2025)
This paper is a description of the compositional and realization processes behind Recordare – Madrigale recitato per suoni elaborati, a 7’ minutes-long acousmatic piece that I have created between 1996 and 2001. Recordare features some interesting macro-granular techniques which meet specific compositional and aesthetic demands and requirements. Furthermore, although it is an acousmatic work, its fully automated building process allows constant recreation and adaptation to different spaces and venues. Finally, Recordare has been developed and written with longevity in mind: it was conceived entirely with Free Software tools in order to guarantee its longterm sustainability and reproducibility.